PENGARUH KEEFEKTIFAN KEPEMIMPINAN TERHADAP KEPUASAN KERJA DI PERUSAHAAN BERBASIS KELUARGA - Sentot Imam Wahjono (STIE Perbanas Surabaya, 2013)
Small and Medium Enterprises (SMEs) in general, grow and develop from the bottom armed with the spirit of entrepreneurship. After survived and developed into a company, usually a family business that is driven by human resources that have a family linkage to each other. As a family business that emphasizes harmony, need a central figure as a leader capable of moving the company effectively. The aim of this research is to analyze the relationship of leadership effectiveness on job satisfaction in small and medium-sized enterprises based on family. The effectiveness of leadership in family firms in the model of situational leadership is largely determined by the adjustment of the maturity of the employees with the leadership style practiced. In the event of compliance hence could be expected would be easy to achieve corporate objectives include achieving sustained earnings growth that is sustainable. One indicator of leadership effectiveness is the satisfaction and performance improvement. This research examines the relationship between leadership effectiveness with satisfaction. Lead- ership model is using the situational leadership theory of Hersey-Blanchard. The results turned out to support the theory that there is a positive and significant relationship between leadership effectiveness and job satisfaction.